Radiofrequency Electromagnetic Field Exposure Amplifies the Detrimental Effects of Fetal Hyperglycemia in Zebrafish Embryos - Derya Cansız; Merih Beler; Gizem Eğilmezer; Semanur Işıkoğlu; Zülal Mızrak; İsmail Ünal; Selçuk Paker; Ahmet Ata Alturfan; Ebru Emekli Alturfan (European Journal of Biology)
Objective: Radiofrequency electromagnetic field (RF-EMF) exposure during the embryonic period can cause defects in the development of the fetus. The study’s aim is to evaluate the effects of RF-EMF on the lipid accumulation, oxidant-antioxidant system parameters, locomotor activities, and gene expressions of insulin and leptin as genes related to insulin resistance in fetal hyperglycemia-induced zebrafish embryos. Materials and Methods: The study exposed zebrafish embryos to RF-EMF (60 min) and glucose (5%) every day until 96 hours post fertilization (hpf). The study measured lipid peroxidation (LPO), superoxide dismutase, nitric oxide (NO), glutathione S-transferase (GST), and glutathione (GSH) levels to observe the oxidative stress status. The study monitored the development of the zebrafish embryos under a microscope, performed a locomotor activity analysis, measured acetylcholinesterase activity, and conducted oil red O staining to determine lipid accumulation. The study used reverse transcription polymerase chain reactions (RT-PCRs) to determine the expressions of ins and lepa by using RT-PCR. Results: Both the glucose and RF-EMF applications decreased locomotor activity and increased the LPO and NO levels as oxidative damage indicators. Applying RF-EMF alone increased GST and GSH levels, while applying RF-EMF and glucose showed a decrease in the antioxidant defense systems. ins expression increased in the glucose and RF-EMF groups, while lepa expression increased in the glucose group and decreased in the RF-EMF group. Conclusion: The harmful effects of hyperglycemia and RF-EMF exposure during the fetal period on embryo development need to be supported by studies to confirm the changes the current study has identified at the gene and protein levels.